Visionary Leadership Boosting Innovation and Digital Transformation in Technology-Based MSMEs - Awaludin; Nuzuliati (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the relationship between visionary leadership and the level of innovation in technology-based MSMEs in Medan City. The approach used is quantitative with a correlational descriptive design. The research sample consisted of 93 MSME actors who were selected using stratified random sampling techniques. The data collection instrument is a closed questionnaire with a Likert scale, which has been tested for validity and reliability. The results of the analysis show that visionary leadership is in the high category, while the level of innovation of MSMEs is in the medium to high category. The Pearson correlation test yielded a value of r = 0.671 which showed a strong and positive relationship between the two variables. The t-test showed that the relationship was statistically significant (t-count = 8.63 > t-table = 1.99). These findings confirm that visionary leadership plays an important role in driving the adoption of innovation in the MSME sector, especially in the use of digital technology. Thus, strengthening the capacity of visionary leadership is a key strategy to increase the competitiveness and sustainability of MSMEs in the era of digital transformation.